Precision tests of third-generation four-quark operators: one- and two-loop matching - Ulrich Haisch; Luc Schnell (Journal of High Energy Physics)
Abstract We calculate the one- and two-loop matching corrections in the Standard Model effective field theory (SMEFT) that impact electroweak precision measurements and flavour physics observables, focusing on the contributions of third-generation four-quark operators. Our results provide a crucial ingredient for a model-independent analysis of constraints on beyond the Standard Model physics that primarily affects the sector of third-generation four-quark operators. Concise analytic expressions are provided for all considered precision observables, which should facilitate their inclusion into global SMEFT analyses.